Development of Interesting Step-climbing Styles - Chen, J. J.; Weng, L. Y.; Peng, S. M.; Tsai, M. W.; Hsu, M. J.; Huang, C. C.; Lin, S. L.; Liing, R. J.; Hsien, H. W.; Liao, Y. H. (Methods of Information in Medicine, 2005)
Objectives: This study was to investigate the influence of stepping styles (forward, side, and cross steppings) and inclinations (25 and 45 degrees) on cardiorespiratory responses (C-R responses).Methods: Twenty volunteers were recruited and randomly arranged into two ten-people groups, exercising on step-climbing machines respectively of 25 and 45 degrees of inclination. C-R responses were recorded during each test which lasted for six minutes at 50 steps per minute on a step-climbing machine.Results: The group on 25-degree inclination had significantly lower C-R responses than the group on 45-degree inclination. Although only small differences, probably statistically insignificant, were found among the three step-climbing styles, these differences showed interesting trends independent of inclination.Conclusions: Climbing stairs with the three interesting step-climbing styles in this study could be considered as an exercise of moderate intensity (60-80% HRmax). Climbing on 25-degree inclination at 50 steps per minute is recommended for less fit individuals because of lower cardiovascular stress as compared with on 45-degree inclination.
Keywords: Exercise; oxygen consumption; exertion; blood pressure